ANALISIS KARAKTERISTIK DAN SELERA KONSUMEN KFC BG JUNCTION SURABAYA - Darwis, Kevin Andres; Parsudi, Setyo; Amir, Indra Tjahaja (Berkala Ilmiah AGRIDEVINA, 2020)
High mobility patterns of life demand that anything be done practically, and save time, so that with a new lifestyle makes people often eat out, consequently many restaurants have sprung up especially fast food restaurants. Competition between companies is now about satisfying consumers. So the company must make the right marketing strategy. But in this KFC restaurant has a problem that is decreased profits. This study aims to find out about the characteristics and tastes of KFC BG Junction consumers as a consideration for KFC restaurants in the formulation of strategies. The study was conducted at the KFC BG Junction Surabaya restaurant. This study was included in a qualitative study with 50 respondents and the sampling technique was with an accidental sampling technique. The analysis is used to determine the characteristics and tastes of consumers with descriptive analysis. Results Characteristics of KFC BG Junction consumers are generally female respondents in high school education which incidentally as students with monthly income of Rp. 1,000,000 / month activities outside the home. While KFC BG Junction consumer tastes, generally like the spicy taste of crispy chicken upper thighs, beef or chicken burgers, and KFC bento sasus black pepper, while the most preferred side menu is french fries and drinks that are favored by float mocha and cash payment methods. So that strategies need to be made based on the general consumer. DOI : https://doi.org/10.33005/adv.v9i1.2144